Animal Law in South Africa: “Until the lions have their own lawyers, the law will continue to protect the hunter” - Amy P. Wilson (Universitat Autonoma de Barcelona. Facultat de Dret, 2019)
Despite the importance of animals to South Africa, animal law is not yet recognized a separate distinct area of law. In an attempt to rectify this, the article provides a high level introduction to this highly complex field. By providing background and context into historical and current injustices regarding humans and animals, it alleges that the current legal system has failed to provide adequate protection to either group. By analyzing the existing regulatory framework and case law, it lays out the realities of obtaining better protection for animals in law. It then argues why it is particularly critical for the country to consider animal interests both individually and collectively with human interests by providing examples of how these interests intersect in practice. It suggests an approach for future protection efforts and concludes by providing some opportunities going forward for animal law reform in South Africa.